A covalent inhibitor targeting the papain-like protease from SARS-CoV-2 inhibits viral replication. Issue 16 (4th April 2023) - Han, Hesong; Gracia, Albert Vallejo; Røise, Joachim J.; Boike, Lydia; Leon, Kristoffer; Schulze-Gahmen, Ursula; Stentzel, Michael R.; Bajaj, Teena; Chen, Dake; Li, I.-Che; He, Maomao; Behrouzi, Kamyar; et al.
Abstract : Compound 1 is a covalent inhibitor of SARS-CoV-2 PLpro that inhibits viral replication and has low non-specific reactivity with thiols. Abstract : Covalent inhibitors of the papain-like protease (PLpro) from SARS-CoV-2 have great potential as antivirals, but their non-specific reactivity with thiols has limited their development. In this report, we performed an 8000 molecule electrophile screen against PLpro and identified an α-chloro amide fragment, termed compound 1, which inhibited SARS-CoV-2 replication in cells, and also had low non-specific reactivity with thiols. Compound 1 covalently reacts with the active site cysteine of PLpro, and had an IC50 of 18 μM for PLpro inhibition. Compound 1 also had low non-specific reactivity with thiols and reacted with glutathione 1–2 orders of magnitude slower than other commonly used electrophilic warheads. Finally, compound 1 had low toxicity in cells and mice and has a molecular weight of only 247 daltons and consequently has great potential for further optimization. Collectively, these results demonstrate that compound 1 is a promising lead fragment for future PLpro drug discovery campaigns.